Accounting as a Social Construction: Interpreting the Meaning of Transparency and Responsibility in the Modern Business World (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study aims to understand how accounting functions as a social construction in shaping the meaning of transparency and responsibility in the modern business world. Accounting has long been viewed as a technical, neutral, and objective system; however, both financial and non-financial reporting practices also reflect the values, ideologies, and moral consciousness embedded within organizations. Using a qualitative interpretive approach within the framework of social constructivism (Berger & Luckmann, 1966), this study explores the meanings constructed by accounting practitioners through social interactions, organizational culture, and reporting policies. Data were collected through in-depth interviews, participatory observations, and document analysis of corporate reports, and were analyzed using interpretative thematic analysis. The results reveal that transparency and responsibility are not merely formal obligations but the outcomes of social processes involving the externalization of values by leaders, the objectivation of those values through reporting systems, and their internalization within individual moral awareness. In this context, accounting functions as a social language that reflects organizational morality, legitimacy, and identity. Organizations with participatory and reflective cultures are found to develop more authentic transparency, while bureaucratic structures tend to produce symbolic transparency. Theoretically, this study contributes to the discourse of critical accounting by asserting that accounting numbers and reports are socially constructed artifacts imbued with values. Practically, the findings highlight the importance of ethical leadership, reflective culture, and social dialogue as foundational elements for implementing authentic transparency and sustainable corporate responsibility.